Effectiveness of Rectal Suction Biopsy in Diagnosing Hirschsprung Disease - Keyzer-Dekker, Claudia M. G.; Sloots, Cornelius E.; Linschoten, Irene K. Schokker-van; Biermann, Katharina; Meeussen, Conny; Doukas, Michael (European Journal of Pediatric Surgery, 2016)
Introduction Rectal suction biopsy (RSB) is performed on clinical and radiological suspicion of Hirschsprung disease (HD). Positive histochemical staining for acetylcholinesterase in the lamina propria mucosa and muscularis mucosa together with the absence of ganglion cells in the submucosa confirms HD. A second RSB or a full-thickness biopsy is done in case of doubt. The primary aim of the study was to evaluate the effectiveness of RSB in diagnosing HD. In addition, the results of RSB in preterm born infants were analyzed.Methods This retrospective study included all infants younger than 1 year who had RSB for HD suspicion from January 2004 to April 2014. All histopathological results were reviewed. Sensitivity, specificity, positive, and negative predictive values of the first RSB were calculated.Results In total, 183 patients (99 boys, mean age 11 weeks) were included. HD was diagnosed in 55 patients (30%). A second biopsy was performed in 12/55 patients (22%), which confirmed HD in 9 patients. One patient did not undergo a second biopsy, but HD was excluded based on clinical follow-up. Thus, HD was eventually excluded in 4 of the 55 patients with a positive first RSB. HD was excluded in the first biopsy in 128 patients (70%). In 19 of those (15%), a second biopsy was done, which led to the diagnosis of HD in 10 patients. Two patients with negative biopsy results were still operated on because of the high clinical suspicion for HD, and the histopathological analysis on the operative specimen confirmed HD. Thus, HD was eventually diagnosed in 12 out of 128 patients. Thus, the sensitivity of the first RSB was 81% and the specificity was 97%. The positive predictive value was 93% and the negative predictive value was 91%. A subanalysis for the 38 preterm born infants was done, with a mean conceptional age at the time of biopsy of 44 weeks (range 34–82). Sensitivity and specificity of RSB were 83 and 97%, respectively, with one false-positive and one false-negative results.Conclusion The overall sensitivity of the RSB was 81%, with 12 false-negative results, in which cases extra biopsies had been necessary. The specificity was 97%, with four false-positive findings. We found that RSB can also be reliably and safely performed in preterm born infants, which implies there is no reason to postpone a RSB in those infants. New methods, such as calretinin staining, must be considered to achieve better effectiveness of the RSB for diagnosing HD.
Keywords: Hirschsprung disease; rectal suction biopsy; immunohistochemistry; ganglion cells; acetylcholinesterase activity